Protocolos de terapia fotodinâmica utilizados em endodontia e sua ação antimicrobiana : uma revisão sistemática - Bonacina, Gabriela (2019)
The possibility of maintenance of microorganisms inside the root canals, even after the chemical-mechanical preparation (PQM) maneuvers, promotes the search for new strategies that optimize the disinfection power of the endodontic treatment. Photodynamic therapy (PDT) emerges as a promising alternative when it is associated to the irrigation protocol, with the objective of broadening the therapeutic arsenal of antimicrobial action. However, there is no consensus among the authors about their application protocol. The objective of the present study was to conduct a systematic review of the literature to identify, describe and quantify the different PDT protocols already described. The search strategy was applied to the following electronic databases, without language and date restrictions: PubMed, PubMed Central (PMC), Embase, Scopus, EBSCO Dentistry and Oral Science Source (DOSS) and Virtual Health Library (VHL). 88 studies were included, being 68 laboratory, 3 in animals and 17 in humans. Based on inclusion and exclusion criteria, two independent reviewers assessed the methodological quality of the included studies, based on adapted versions of the risk of bias assessment tools. The following data were extracted: name of authors, date of publication, country of study development, type and study design (clinical or laboratory), sample size, main outcome, method of analysis, light emitting device power, wave, associated photosensitizer and time of application. In the case of laboratory studies, the types of bacterial strains tested and their concentration are included. When not reported, the percent reduction of bacterial load was calculated. The main outcome variable was the photodynamic therapy protocols applied, and the secondary outcome was the reduction percentage of microbial load (PDT protocols associated or not to the chemo-mechanical prepare). The aggregate mean of the microbial reduction percentage of the different PDT protocols among the laboratory studies when associated to the chemical-mechanical prepare was 97.73.8%, when not associated to the chemical-mechanical prepare was 44.026.1% and, when associated to the use of irrigation solutions was 36,122.3%. Due to the heterogeneity of the studies, it was not possible to perform the meta-analysis of the data. Despite the great variability of the included studies, the present systematic review was able to expose the current lack in the literature, of studies with adequate bias control to evaluate, laboratory and clinically, the antimicrobial capacity of the different PDT protocols. In addition, in order to elect a PDT protocol as a gold-standard, new investigations must be dedicated to compare the antimicrobial efficacy among the protocols variables, especially the type and the concentration of the photosensitizer and the pre-irradiation and irradiation times.